Dietary protein, amino acids and type 2 diabetes mellitus: a short review - Mensink, Marco (Frontiers in Nutrition, 2024)
Diabetes is a widespread metabolic disorder and results from insulin resistance and impaired insulin secretion. Modifiable factors like diet, physical activity, and body weight play crucial roles in diabetes prevention, with targeted interventions reducing diabetes risk by about 60%. High-protein consumption, above the recommended intake of 0.8 g/kg body weight per day, have often explored in relation to diabetes risk. However the relationship between dietary protein and diabetes is multifaceted. Observational studies have linked high total and animal protein intake to an increased risk of type 2 diabetes, particularly in obese women. Elevated levels of branched-chain amino acids (BCAA), which can result from dietary intake, protein breakdown, as well as an impaired catabolism, are strong predictors of cardiometabolic risk and insulin resistance. With several mechanism linking BCAA to insulin resistance. On the other hand, intervention studies suggest that high-protein diets can support weight loss and improve cardiometabolic risk factors. However, the impact on insulin sensitivity and glucose homeostasis is not straightforward. Proteins and amino acids stimulate both insulin and glucagon secretion, influencing glucose levels, but chronic effects remain uncertain. This short narrative review aims to provide an update on the relationship between increased dietary protein intake, amino acids, insulin resistance and type 2 diabetes, and to describe protein recommendations for type 2 diabetes.